A243 CLOSTRIDIUM DIFFICILE COLITIS: DIAGNOSTIC DIFFICULTY WITHOUT DIARRHEA. (15th March 2019) - Jawaid, N; Cohen, L
Abstract: Background: Clostridium Difficile infection leading to colitis is a common occurrence after antibiotics use. It clinically presents with crampy abdominal pain, frequent watery stools and leukocytosis. We present two cases of culture-proven C. difficile and endoscopically visualized pseudomembranous colitis in patients without diarrhea. Aims: To discuss the current clinical diagnostic approach towards diagnosing C. Difficile colitis in patients with and without diarrhea. To present two cases of patients with endoscopic, biopsy and cultures proven C. Difficile colitis despite having no diarrhea and the diagnostic difficulties that surround such cases in clinical practice. Methods: Two patients presented without diarrhea but found to have C. difficile colitis that improved symptomatically with treatment. Results: CASE 1 : 86-year-old female presented with intermittent abdominal cramping increasing in severity over 2 weeks. She showed no other infectious signs or symptoms, denied fevers, diarrhea and she had no leukocytosis. CT scan showed colitis and fat stranding involving ascending and transverse colon. Colonoscopy showed mucosal edema with patchy pseudomembranes seen throughout transverse and ascending colon. Stool cultures taken during colonoscopy returned positive for C. difficile. After starting oral vancomycin, her abdominal pain resolved within 2 days and she was discharged home to complete a 10-day course of vancomycin. CASE 2 : 81-year-old male with recurrent gram-negative bacteremia and an ileal-conduit fistula referred for possible GI source of infection. He had taken several courses of antibiotics for his recurrent bacteremia. He described subjective fevers. He denied diarrhea and had no leukocytosis. CT scan showed left and right-sided colitis, sparing of transverse colon. Colonoscopy showed mild pancolitis with patchy pseudomembranes seen throughout. Repeat cultures taken during colonoscopy returned positive for C. difficile. He was started on oral vancomycin resolving fevers and general malaise. He was discharged shortly thereafter with ID follow up as an outpatient. The cause of his gram-negative bacteremia was not found. Conclusions: C. difficile colitis typically occurs after a course of antibiotics manifest by watery diarrhea, leukocytosis and abdominal pain. It is generally not considered in the differential diagnosis for patients who are not experiencing diarrhea. Even the most recent American College of Gastroenterologists guideline on diagnosis, treatment, and prevention of Clostridium difficile infections states to test stool cultures only if the patient is having diarrhea. This case series of two patients presenting with imaging, endoscopic and culture proven C. difficile colitis without diarrhea with symptomatic improvement after treatment illustrates that C. difficile colitis should still be on the differential diagnosis of abdominal pain even when diarrhea is not present. Funding Agencies: None